Development of Digital Literacy Assessment Instruments in Physics Learning at MAN 5 Batanghari - Prameswari, Nirmala; Darmaji, Darmaji; Kurniawan, Dwi Agus (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2024)
This research is motivated by the importance of students' digital literacy skills in the learning process. This research is a type of descriptive qualitative research, with the aim of knowing how the digital literacy assessment instrument was developed. The population of this study were students at MAN 5 Batangahari, from which the population was sampled using a purposive sampling technique, namely class X students at MAN 5 Batanghari who majored in MIPA, totaling 35. The data collection instrument used was structured interview sheets. for teachers and students. Then data analysis in this study used Miles and Huberman's analysis which consisted of data collection, data reduction, data presentation, and drawing conclusions. The result of this study is the need to develop a digital literacy assessment instrument that is in accordance with digital literacy indicators and learning objectives because there are not many assessment instruments available to measure digital literacy.